Factors Affecting the Compliance of Pulmonary TB Patients in Drug Consumption at the Batumarta II Health Center, Lubuk Raja District, Ogan Komaring Regency, Ulu, South Sumatra in 2024 - Prisca, Tety Okta; Nuraini, Nuraini; Nasution, Ramadhani Syafitri (PROMOTOR, 2025)
Pulmonary tuberculosis (TB) is a direct infectious disease and is a major threat to human resource development, the World Health Organization (WHO) said the number of people diagnosed with tuberculosis in 2021 globally was 10.6 million cases, plus treatment failure was also a major contributor to the incidence of pulmonary tuberculosis in the community. The purpose of this study is to analyze the factors that affect the compliance of TB patients in drug consumption at the Batumarta II Health Center. This type of research is an analytical survey with a retrospective design. The research was conducted at the Batumarta II Health Center in 2024. By using the total sampling technique, which is as many as 50 respondents. To analyze the data, a logistic regression test was used. Based on the results of the study, it was found that there was a relationship between drug consumption compliance and variables, namely knowledge (p=0.000), attitude (P=0.000), health workers (p=0.021), family support (p=0.001) and culture (p=0.000), but there was no effect on the availability of OAT with drug consumption compliance because of the P value (p=1,000) at the Batumarta II Health Center, South Sumatra. Based on the results of the study, it can be concluded that the factors that affect drug consumption compliance at the Batumarta II Health Center are knowledge, attitudes, health workers, family and cultural support. The most dominant factor affecting drug consumption compliance at the Batuamrta II Health Center is knowledge that has  an Exp(B) or Odd Ratio value of 37,200. Suggestions for making counseling programs on factors affecting patient compliance in drug consumption both to families of patients and pulmonary TB patients to increase public knowledge about the correct TB treatment methods and patterns in order to maximize healing outcomes.